2002
DOI: 10.1002/syn.10125
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of synapse formation between Lymnaea heart motor neuron and muscle fiber is maintained in vitro in a soma–muscle configuration

Abstract: Precise neuronal connectivity during development is subservient to all nervous system functions in adult animals. However, the cellular mechanisms that mastermind this neuronal connectivity remain largely unknown. This lack of fundamental knowledge regarding nervous system development is due in part to the immense complexity of mammalian brain, as cell-cell interactions between defined sets of pre- and postsynaptic partners are often difficult to investigate directly. In this study, we developed a novel model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…By extending these data, some specific synaptic-like proteins of vesicles, synapsin, and synaptophysin that had been detected in neuromuscular junctions of mammalian cultured cells (DeCamilli et al 1988) have been found in the neuronal cells of snails Aplysia punctata and Helix pornatia (Chin et al 1990;Bongiovi et al 1992;Cibelli et al 1996). Moreover, synapse formation between the heart motor neuron and muscle fiber of the snail Lymnaea stagnalis has been reconstructed in vitro (Lee et al 2002).…”
Section: Introductionmentioning
confidence: 95%
“…By extending these data, some specific synaptic-like proteins of vesicles, synapsin, and synaptophysin that had been detected in neuromuscular junctions of mammalian cultured cells (DeCamilli et al 1988) have been found in the neuronal cells of snails Aplysia punctata and Helix pornatia (Chin et al 1990;Bongiovi et al 1992;Cibelli et al 1996). Moreover, synapse formation between the heart motor neuron and muscle fiber of the snail Lymnaea stagnalis has been reconstructed in vitro (Lee et al 2002).…”
Section: Introductionmentioning
confidence: 95%
“…The dissociated cells were subsequently washed three times with defined medium and sedimented at low speed, before plating. Dissociated muscle fibers were kept in defined medium in Costar (Cambridge, MA) dishes at 20°C for 1-4 d (Lee et al, 2002). All neuronal culture procedures were performed as described previously (Syed et al, 1990).…”
Section: Cardiac Muscle Dissociation and Neuron Isolationmentioning
confidence: 99%
“…The synaptic inputs of motoneurons into the heart are conserved even in vitro , i.e. if the muscle fibers and these neurons are kept in culture in close proximity, they will develop functional connections (Lee et al, 2002). Interestingly, even neurites can survive and function without soma in vitro .…”
Section: Excitation Of Heartmentioning
confidence: 99%